Quality management and safety assurance in Horticultural chains of Bangladesh (Research in Agriculture Livestock and Fisheries, 2015)
Horticultural produce, especially fruits and vegetables, are rich sources of phytochemicals, namely vitamins, minerals and antioxidants. Currently, controlling quality and assuring safety of fruits and vegetables in supply chain has become one of the most challenging issues in Bangladesh. Often consumers are dissatisfied with the poor quality produce due mainly to the sub-standard postharvest handling practices. Side by side, the issue of food safety has been emerged as the most serious threat in the context of nutrition security and public health of the country. There are huge concerns over the use of harmful chemicals during production and postproduction stages. The main concerns are related to the presence of heavy metals, chemical residues and microbial contamination. Hence, immediate interventions are needed to stop any malpractice during production and marketing of fruits and vegetables. The recently introduced Food Safety Act 2013 and Formalin Control Act 2014 are two important steps from the Government of Bangladesh to deal with this deep-rooted concern. Apart from laws, various training and awareness programmes are needed so that the relevant stakeholders adopt improved practices to maintain quality and safety of produce along the supply chains. Consumption of good quality, nutritious and safe fruits and vegetables can only be assured if quality and safety control can be ensured at the production (manures, fertilizers, waters, pesticides, plant growth regulators, etc.) and postproduction (during harvesting, sorting, grading, washing, packaging, transporting, storing, processing and marketing) stages. Since, the problem is interdisciplinary and complex, there should have strong coordination among the various groups in the society including producers, traders, processors, policymakers, law enforcing agencies, researchers, physicians, civil society representatives, and other relevant GOs and NGOs in order to prevent the malpractice and improve the quality and safety situation in the horticultural chains of Bangladesh.DOI: http://dx.doi.org/10.3329/ralf.v1i1.22346 Res. Agric., Livest. Fish.1(1): 1-11, Dec 2014